A Study on Implementing Food Safety Management System in Bottling Plant. (15th May 2015) - Singh, Manish Kumar
Abstract: This study provides the need for implementing Food Safety Management System (FSMS) to ensure the safety of the drinking water. Procedural challenges faced in adaptation of ISO 22000:2005 Food Safety Management Standards for a bottling company to achieve its safety goals. For implementing the FSMS, the general and documentation requirement with modular approach and the Management responsibility for their food safety policy, hygienic design, specifying the program for cleaning and sanitisation, equipment maintenance, control for strict raw materials and analysis of critical control point (CCP) are taken care of. For guarantee food safety, before the implementation the Pre-requisite Programs is followed for controlling the generic hazards. The systematic approach for Hazard analysis with the help of a practical approach model gets a control on non-conforming product/material and also for potentially unsafe products. The implementation of FSMS covers all the manufacturing operations, from receipt of raw materials, material storage, processing, packaging, warehousing and distribution.